Nanoindentation Study of Single-Crystalline and (101)-Oriented Nanotwinned Cu. (1st January 2019) - Yang, Cheng-Hsien; Lee, Cheng-Yu; Huang, Bau-Chin; Lin, Ping-Chou; Ho, Cheng-En
Abstract : Copper (Cu) is the interconnect material of choice in the integrated circuit (IC) devices and printed circuit boards (PCBs) due to its low electrical resistivity, high electromigration resistance, and excellent mechanical, chemical, and thermodynamical characteristics. In this study, the relationship between the Cu mechanical properties [e.g., hardness ( H ), Young's modulus ( E ), and stiffness ( S )] and its crystallographic microstructure, including single-crystalline Cu and highly (101)-oriented nanotwinned Cu (nt-Cu), were characterized via nanoindentation, electron backscatter diffraction (EBSD), focused ion beam (FIB), and transmission electron microscopy (TEM). H, E, and S depended on the crystallographic orientation of single-crystalline and nt-Cu. A theoretical calculation based on the Schmid's law was made to rationalize the dependence of the Cu mechanical characteristics on the crystallographic orientation. The information associated with this orientation-dependent behavior is of great importance to the IC and PCB communities, particularly in developing the ultrafine Cu interconnect technique.